2003
DOI: 10.1105/tpc.013011
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light-Dependent in Vivo and in Vitro Phosphorylation of Arabidopsis Cryptochrome 1

Abstract: Cryptochromes are photolyase-like blue/UV-A light receptors that regulate various light responses in animals and plants. Arabidopsis cryptochrome 1 (cry1) is the major photoreceptor mediating blue light inhibition of hypocotyl elongation. The initial photochemistry underlying cryptochrome function and regulation remain poorly understood. We report here a study of the blue light-dependent phosphorylation of Arabidopsis cry1. Cry1 is detected primarily as unphosphorylated protein in etiolated seedlings, but it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
200
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(214 citation statements)
references
References 49 publications
(48 reference statements)
10
200
1
3
Order By: Relevance
“…CRY2 is particularly important in retarding hypocotyl growth in response to low intensity blue light, whereas CRY1 has a prevalent role in response to higher blue light intensity . Furthermore, CRY1 phosphorylation kinetics and activation exhibits a positive correlation with blue light intensity in direct contrast to CRY2, which exhibits a negative correlation with blue light intensity (Shalitin et al, 2002(Shalitin et al, , 2003. Thus, although CRY1, but not CRY2, has been shown to mediate a response to higher irradiances, a role for CRY1 during changes in irradiance and the high light response has not been previously described.…”
Section: Discussionmentioning
confidence: 59%
“…CRY2 is particularly important in retarding hypocotyl growth in response to low intensity blue light, whereas CRY1 has a prevalent role in response to higher blue light intensity . Furthermore, CRY1 phosphorylation kinetics and activation exhibits a positive correlation with blue light intensity in direct contrast to CRY2, which exhibits a negative correlation with blue light intensity (Shalitin et al, 2002(Shalitin et al, , 2003. Thus, although CRY1, but not CRY2, has been shown to mediate a response to higher irradiances, a role for CRY1 during changes in irradiance and the high light response has not been previously described.…”
Section: Discussionmentioning
confidence: 59%
“…It was found that both AtCRY1 and AtCRY2 are phosphorylated in vivo upon blue light exposure (Shalitin et al 2002;. Later, it was shown that purified AtCRY1 bound ATP stoichiometrically and that both AtCRY1 (Bouly et al 2003;Shalitin et al 2003) and human CRY1 (Bouly et al 2003) were autophosphorylated in a FAD-and blue-light-dependent manner. In line with these biochemical findings, the crystal structure of the AtCRY1 PHR domain contained an ATP analog in the cavity leading to FAD where the pyrimidine dimer binds in photolyase (Brautigam et al 2004).…”
Section: Protein-protein Interactionsmentioning
confidence: 99%
“…The C-terminal domain is important for either localization or protein stability, and its expression in Arabidopsis results in constitutive growth (Lin and Todo, 2005). Plant CRYs are phosphorylated under illumination, and gene expression control ranges from protein interactions to direct chromatin interactions (Shalitin et al, 2002(Shalitin et al, , 2003Lin and Todo, 2005). In mice, CRYs can affect the activity, interaction, degradation, or nuclear trafficking of circadian clock components in lightindependent manner (Griffin et al, 1999;Lin and Todo, 2005).…”
mentioning
confidence: 99%